Point-of-care solution for osteoporosis management : design, fabrication, and validation of new technology. - Khashayar, Patricia (Springer, 2017)
This book addresses the important clinical problem of accurately diagnosing osteoporosis, and analyzes how Bone Turnover Markers (BTMs) can improve osteoporosis detection. In her research, the author integrated microfluidic technology with electrochemical sensing to embody a reaction/detection chamber to measure serum levels of different biomarkers, creating a microfluidic proteomic platform that can easily be translated into a biomarker diagnostic. The Osteokit System, a result of the integration of electrochemical system and microfluidic chips, is a unique design that offers the potential for greater sensitivity. The implementation, feasibility, and specificity of the Osteokit platform is demonstrated in this book, which is appropriate for researchers working on bone biology and mechanics, as well as clinicians.